2008
DOI: 10.1097/mpa.0b013e3181735ccb
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin Inhibits the GLUT-1 Glucose Transporter and the Phosphoinositide 3-Kinase/Akt Pathway in Human Pancreatic Cancer Cells

Abstract: Our results demonstrate that the flavonoid apigenin decreases glucose uptake and downregulates the GLUT-1 glucose transporter in human pancreatic cancer cells. In addition, the inhibitory effects of apigenin and the PI3K inhibitors on GLUT-1 are similar, indicating that the PI3K/Akt pathway is involved in mediating apigenin's effects on downstream targets such as GLUT-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
133
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(137 citation statements)
references
References 22 publications
3
133
1
Order By: Relevance
“…The PI3K/Akt pathway has been shown to promote both GLUT-1 cell-surface trafficking and activity (14,15). The activation and phosphorylation of PI3K/Akt are not only well-recognized regulators of cell growth, survival and angiogenesis, but they also play an important role in promoting glucose metabolism (28).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The PI3K/Akt pathway has been shown to promote both GLUT-1 cell-surface trafficking and activity (14,15). The activation and phosphorylation of PI3K/Akt are not only well-recognized regulators of cell growth, survival and angiogenesis, but they also play an important role in promoting glucose metabolism (28).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to the insulin-responsive glucose transporter GLUT-4, GLUT-1 cell-surface localization is controlled by extrinsic signals. Among the signaling pathways initiated in cell activation, the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt) pathway has been shown to promote both GLUT-1 cell-surface trafficking and activity (14,15).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has shown that in human tongue squamous carcinoma (SCC-9) and human esophageal cancer (both KYSE-510 and OE33), after exposure to apigenin, the level of cells in the G1 phase (when the cells grow in size and mRNA and high amounts of protein are synthesized) decreased, while the level of cells in the third stage of interphase (the G2 phase) increased. 16 This is associated with the down-regulation of protein cyclin B1 and the up-regulation of p53-inducible gene 3 and protein p21-WAF1. P21-WAF1 is responsible for G1 phase arrest and the G2/M checkpoint, and apigenin in concentration levels higher than 30 μM increases the transcription of this protein.…”
Section: Modification Of the Cell Cyclementioning
confidence: 99%